2015
DOI: 10.1186/s12889-015-1671-z
|View full text |Cite
|
Sign up to set email alerts
|

Noise exposure and hypertension: investigation of a silent relationship

Abstract: BackgroundNoise is an important occupational hazard worldwide and hypertension a well-known risk factor for cardiovascular disease, which is currently the greatest cause of disability retirement worldwide. The association between noise exposure and auditory effects is well documented in the biomedical literature, but the same is not true about exposure to different levels of noise and extra-auditory effects. It has been shown that noise exposure levels to be considered for non-auditory effects may not be the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 25 publications
2
61
3
4
Order By: Relevance
“…However, most studies find results broadly consistent to ours. De Souza et al ,29 in an occupational noise exposure study at higher noise exposure levels (>75 dB) and including younger subjects compared with the present study, found an OR for hypertension of 1.56 (95% CI 1.13 to 2.17). A recent meta-analysis of five studies on the effect of noise on the prevalence/incidence of hypertension,6 which did not include the HYENA study, found an OR of 1.63 for exposure to aircraft noise versus non-exposure, a finding consistent with ours (although it should be noted that the definition of ‘exposure’ was differently defined between studies).…”
Section: Discussioncontrasting
confidence: 45%
“…However, most studies find results broadly consistent to ours. De Souza et al ,29 in an occupational noise exposure study at higher noise exposure levels (>75 dB) and including younger subjects compared with the present study, found an OR for hypertension of 1.56 (95% CI 1.13 to 2.17). A recent meta-analysis of five studies on the effect of noise on the prevalence/incidence of hypertension,6 which did not include the HYENA study, found an OR of 1.63 for exposure to aircraft noise versus non-exposure, a finding consistent with ours (although it should be noted that the definition of ‘exposure’ was differently defined between studies).…”
Section: Discussioncontrasting
confidence: 45%
“…However, the effect of noise exposure upon blood pressure is still inconclusive as both hypertension and hypotension has been reported (de Souza et al, 2015;Lercher and Widmann, 2013;Lercher et al, 2014). This inconsistency may be the product of limitations in adjustment for confounders such as air pollution exposure, which is a key risk factor for increased blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…29 Similarly, with an opinion that suggests getting older, the higher the likelihood of developing high blood pressure. As we age, blood pressure increases gradually as the elasticity of the vessels diminishes.…”
Section: Discussionmentioning
confidence: 99%